2013
DOI: 10.1063/1.4826322
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton microscopic imaging of histological sections without hematoxylin and eosin staining differentiates carcinoma in situ lesion from normal oesophagus

Abstract: Multiphoton microscopy (MPM) has become a powerful, important tool for tissues imaging at the molecular level. In this paper, this technique was extended to histological investigations, differentiating carcinoma in situ (CIS) lesion from normal oesophagus by imaging histological sections without hematoxylin and eosin (H&E) staining. The results show that the histology procedures of dehydration, paraffin embedding, and de-paraffinizing highlighted two photon excited fluorescence of cytoplasm and nucleolus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…23 In addition, we found that the sample processing also led to the loss of NAD(P)H and FAD, which destroyed the TPEF signals that can be used as standard biomarkers of epithelium and whose fluorescence ratio (redox ratio) was indicative of the cellular metabolic state. 23 In addition, we found that the sample processing also led to the loss of NAD(P)H and FAD, which destroyed the TPEF signals that can be used as standard biomarkers of epithelium and whose fluorescence ratio (redox ratio) was indicative of the cellular metabolic state.…”
Section: Mpm Imaging Instrumentationmentioning
confidence: 94%
See 2 more Smart Citations
“…23 In addition, we found that the sample processing also led to the loss of NAD(P)H and FAD, which destroyed the TPEF signals that can be used as standard biomarkers of epithelium and whose fluorescence ratio (redox ratio) was indicative of the cellular metabolic state. 23 In addition, we found that the sample processing also led to the loss of NAD(P)H and FAD, which destroyed the TPEF signals that can be used as standard biomarkers of epithelium and whose fluorescence ratio (redox ratio) was indicative of the cellular metabolic state.…”
Section: Mpm Imaging Instrumentationmentioning
confidence: 94%
“…23,25 For high-resolution imaging, a Plan-Neofluar objective (40× and NA ¼ 0.75, Zeiss) was employed in MPM examination. 23,25 For high-resolution imaging, a Plan-Neofluar objective (40× and NA ¼ 0.75, Zeiss) was employed in MPM examination.…”
Section: Mpm Imaging Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonlinear optical imaging system has been previously described [15,16]. In general, nonlinear optical images were obtained by an inverted microscope (LSM 510 META, Zeiss, Germany) equipped with a mode-locked femtosecond Ti: sapphire laser (Mira 900-F; Coherent, Inc.) at an excitation wavelength of 810 nm.…”
Section: Nonlinear Optical Imaging Systemmentioning
confidence: 99%
“…Recently, multiphoton microscopy (MPM) based on two-photon excited fluorescence (TPEF) and second harmonic generation (SHG) have demonstrated the potential for noninvasive visualization of tissue architecture at the cellular level [17,18]. Such methods have exhibited the ability to detect biological tissues and changes in these tissues with high resolution and high sensitivity.…”
Section: Introductionmentioning
confidence: 99%